1986
DOI: 10.1007/bf01407456
|View full text |Cite
|
Sign up to set email alerts
|

Activity of peripheral sympathetic efferent nerves in experimental subarachnoid haemorrhage

Abstract: The origin and pathomechanism of vegetative disturbances in patients suffering from subarachnoid haemorrhage are not completely clarified. Since some of these alterations in vegetative functions may well be attributed to acute changes in sympathetic activity, we initiated a study to investigate this modality in experimentally induced subarachnoid haemorrhage. Experiments were performed on 51 cats, anaesthetized with alpha-chloralose and urethane, immobilized and artificially ventilated. Compound electrical dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1987
1987
2006
2006

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 37 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…Experimental work in cerebrovascular disease yielded controversial results: Graf and Rossi 9 emphasized the epinephrines as mediator between sympathetic activation and clinical symptoms and signs. Hachinski and colleagues 12 14 and other authors22, 25,28,30,34 found that norepinephrines after stroke or intracranial space-occupying processes were more important. In this study the fact that there was no isolated elevation of metanephrine proved the importance of the normetanephrines.…”
Section: Discussionmentioning
confidence: 96%
“…Experimental work in cerebrovascular disease yielded controversial results: Graf and Rossi 9 emphasized the epinephrines as mediator between sympathetic activation and clinical symptoms and signs. Hachinski and colleagues 12 14 and other authors22, 25,28,30,34 found that norepinephrines after stroke or intracranial space-occupying processes were more important. In this study the fact that there was no isolated elevation of metanephrine proved the importance of the normetanephrines.…”
Section: Discussionmentioning
confidence: 96%
“…The most basic effect of an increase in ICP is a massive increase in sympathetic nerve activity causing a sympathetic pressor response (16,44,77,100,116,140). We have demonstrated that ICP elevations and the pressor response are also associated with biogenic amine changes (particularly EPI and NE) in the hypothalamus and brain stem.…”
Section: ---mentioning
confidence: 88%
“…Computed tomography of head was negative for subarachnoid hemorrhage, but angiography revealed a large aneu- tension has been described to be a result of the reflex increase of catecholamine secretion, [6][7][8] and a result of the sympathetic overactivity due to brainstem compression, 9 or due to craniocaudal ischemia. [10][11][12][13] Some animal studies suggest Cushing's response is a late feature, when ICP approaches mean arterial pressure, signalling breakdown of cerebral autoregulation.…”
Section: Case Reportmentioning
confidence: 99%